Fine needle aspirative cytology in the diagnosis of parotid gland neoplasms - Yanet García Fonte; Kenia Betancourt Gamboa; Miriela Betancourt Valladares; Dianelys Busquets Carballo (Gaceta Médica Espirituana)
Background: Aspirative cytology is a technique used in order to differentiate benign and malignant lesions. The parotid is the most frequent site of salivary gland neoplasms and its malignant tumors constitute a disease with low incidence and high mortality.